Potential Antimalarial Activity of Artemether/Lumefantrine/Doxycycline: A Study in Mice Infected with Plasmodium berghei - Udeme Owunari Georgewill; Elias Adikwu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Antimalarial drug resistance is one of the greatest challenges towards eradicating malaria. Exploring new combination therapies can overcome resistance challenges. The present study examined the antiplasmodial effect of artemether/lumefantrine/doxycycline (A/L/D) on a mouse model infected with Plasmodium berghei. Adult Swiss albino mice (22-30g) intraperitoneally infected with blood containing 1x107 Plasmodium berghei were randomly grouped and orally treated daily with D (2.2 mg/kg), A/L (1.71/13.7 mg/kg) and A/L/D. The negative control was treated daily with normal saline (0.2ml) whereas the positive control was treated daily with chloroquine (CQ) (10mg/kg). After treatment, blood samples were assessed for percentage parasitemia and biochemical parameters. Mice were observed for mean survival time (MST). D, A/L and A/L/D produced significant decreases in percentage parasitemia levels at p<0.05; p<0.01 and p<0.001, respectively when compared to negative control. In the curative test, D, A/L and A/L/D produced 60.4%, 70.3%, and 90.0% parasitemia inhibitions, respectively whereas CQ produced 76.0% parasitemia inhibition. D, A/L, A/L/D and CQ produced 63.2 %, 80.1%, 92.3% and 83.6% parasitemia inhibitions, respectively in the suppressive test. D, A/L, and A/L/D prevented Plasmodium berghei-induced alterations in biochemical parameters by increasing packed cell volume, red blood cells, hemoglobin, and high-density lipoprotein and decreasing white blood cells, total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels significantly at p<0.05 and p<0.01 and p<0.001, respectively when compared to the negative control. A/L/D produced significant antiplasmodial activity therefore, it may be used clinically for the treatment of malaria.